Effects of conjugation length and donor-acceptor functionalization on the non-linear optical properties of organic push-pull molecules using density functional theory - Datta, Anindya; Pal, S. (Journal of Molecular Structure-Theochem, 2005)
We consider a series of dipolar organic molecules where the donor groups and the acceptor groups are separated by pi-conjugation like phenyl ring or alkene chains. We have performed extensive quantum chemical calculations based on density functional theory (DFT) to calculate their linear and non-linear optical coefficients. We show that though DFT is known to overestimate the polarizabilities of quasilinear systems,the results with proper inclusion of exchange correlation compare well with the experimental studies. On increasing the pi-conjugation length, the coefficients increase non-linearly. We also vary the donor and the acceptor groups and study the role of chemical modifications on the response properties. Herein we suggest experimental methods by which the molecules may be arranged in non-centrosymmetric fashion in the bulk for device integration. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: DFr; donor-acceptor functionalization; non-linear properties; push-pull molecules

Static hyper-polarizability of open shell molecules computed at the FSMRCCSD level using constrained variational approach - Bag, Arijit; Bhattacharya, S.; Pal, S. (International Conference on Recent Advances in Spectroscopy - Theoretical, Astrophysical and Experimental Perspectives, 2010)
In recent years, there has been a significant development in the analytic derivatives of energy with respect to electric fields based on the state-of-the-art multi-reference coupled-cluster method using Lagrangian based constrained variational approach. So far, the Lagrangian based Fock space multi-reference coupled cluster (FSMRCC) method has been successfully used to calculate electrical dipole moment and polarizability of open shell molecules, particularly, doublet radicals at the ground state and the electronic excited states of closed shell molecules. In this article, Lagrangian based FSMRCC method has been implemented for the first time for calculation of hyper polarizabilites of a few doublet radicals such as OH, OF, NO and NO(2). Orbital-relaxed finite field FSMRCC values are reported for comparison.

Coupled cluster methods for autoionisation resonances - Sajeev, Y.; Ghosh, A.; Vaval, N.; Pal, S. (International Reviews in Physical Chemistry, 2014)
The quantum chemical calculation of autoionisation resonances in many-electron systems is a highly challenging task due to the ionisation continuum involved. Recently, advances were reported where conventionally used ab initio codes can be employed to compute autoionisation resonances. This is made possible by the use of analytical continuation tools such as complex scaling and complex absorbing potential (CAP) in the electronic structure codes. We review the formulation and the use of complex scaling and CAP in coupled cluster methods for the electron correlated calculation of energy position and autoionisation decay rate of resonance states. The application of analytically continued coupled cluster method for the correlated calculation of interatomic or intermolecular Coulombic decay process is also discussed.
Keywords: autoionisation resonances; complex absorbing potential; complex scaling; equation-of-motion coupled cluster; Fock space multi-reference-coupled cluster; intermolecular Coulombic decay

Relativistic equation-of-motion coupled-cluster method using open-shell reference wavefunction: application to ionization potential - Pathak, H.; Sasmal, S.; Nayak, M. K.; Vaval, N.; Pal, S. (Journal of Chemical Physics, 2016)
The open-shell reference relativistic equation-of-motion coupled-cluster method within its four-component description is successfully implemented with the consideration of single- and double- excitation approximations using the Dirac-Coulomb Hamiltonian. At the first attempt, the implemented method is employed to calculate ionization potential value of heavy atomic (Ag, Cs, Au, Fr, and Lr) and molecular (HgH and PbF) systems, where the effect of relativity does really matter to obtain highly accurate results. Not only the relativistic effect but also the effect of electron correlation is crucial in these heavy atomic and molecular systems. To justify the fact, we have taken two further approximations in the four-component relativistic equation-of-motion framework to quantify how the effect of electron correlation plays a role in the calculated values at different levels of theory. All these calculated results are compared with the available experimental data as well as with other theoretically calculated values to judge the extent of accuracy obtained in our calculations.

Electron–nucleus scalar–pseudoscalar interaction in PbF: Z-vector study in the relativistic coupled-cluster framework - Sasmal, S.; Talukdar, K.; Nayak, M.K.; Vaval, N.; Pal, S. (Molecular Physics, 2017)
The scalar–pseudoscalar interaction constant of PbF in its ground state electronic configuration is calculated using the Z-vector method in the relativistic coupled-cluster framework. The precise calculated value is very important to set upper bound limit on (Formula presented.)-odd scalar–pseudoscalar interaction constant, ks, from the experimentally observed (Formula presented.)-odd frequency shift. Further, the ratio of the effective electric field to the scalar–pseudoscalar interaction constant is also calculated which is required to get an independent upper bound limit of electric dipole moment of electron, de, and ks and how these (de and ks) are interrelated is also presented here. © 2017 Informa UK Limited, trading as Taylor & Francis Group

Quantitative comparison of strategies to delay clogging in straight capillaries - Pal, S.; Kulkarni, A. A. (Chemical Engineering Science, 2019)
It is challenging to achieve non-stop flow of a liquid-solid suspension through small channels as it eventually leads to clogging. This paper presents a quantitative comparison of four different techniques for enhancement of solid handling processes in microchannels of two different diameters. These techniques include dosing of the inert gas phase, dosing of the inert and immiscible liquid phase, and changing the wall wettability and multi-point injection, which, in principle, individually follow different mechanisms to delay clogging. An antisolvent based method for precipitation of salt was used to generate solid particles during flow. Clogging time at various flow rates from all the methods was measured and analysed. Irrespective of the method of delaying clogging, the scaling law of clogging time as a function of residence time was seen to remain unchanged. Among these methods, dosing of an inert, immiscible liquid has been identified as the most effective and robust method to delay clogging while enhancing transport of particles in segmented flow.

Retraction: a highly concise and practical route to clavaminols, sphinganine and (+)-spisulosine via indium mediated allylation of α-hydrazino aldehyde and a theoretical insight into the stereochemical aspects of the reaction - Pandey, M.; Chowdhury, P. S.; Dutta, A. K.; Kumar, P.; Pal, S. (RSC Advances, 2019)
A conceptually different approach has been employed for the synthesis of 1,2-amino alcohols by proline-catalyzed α-amination of aldehyde and one-pot indium mediated allylation of the crude α-hydrazino aldehydes. DFT based quantum chemical calculations have been performed to obtain a quantitative explanation of the stereoselectivity of the reaction.